EP.TU.590Making the cut – Tailoring an undergraduate surgical teaching programme a QI project. (28th October 2021) - Koo, Hui Fen; Huttman, Marc; Boardman, Charlotte; Saunders, Michael
Abstract: Aims: This project set out to improve the quality of surgical teaching for final year students on a DGH placement. A four-week programme was introduced and regular modification was undertaken through systematic gathering of feedback. The sessions developed were interactive question-based tutorials, suturing, and on-call simulation with common F1 scenarios. Methods: Material was developed and piloted based on topics the facilitators felt were poorly taught as students. Feedback was gathered by questionnaire after each session comparing the student's confidence before and after, along with suggestions for improvement. This process was repeated through all six rotations. Results: A total of 95 questionnaires were completed. Average confidence increased from 52% to 77%. The programme was expanded based on suggestions to include orthopaedic examinations and plastic surgery. The tutor pool was increased to include more foundation doctors to ensure sustainable weekly delivery. Examples of how suggestions were implemented include: "More difficult cases" – Polling software to monitor difficulty reflected by spread of responses "More images" – Presentation created using images to illustrate orthopaedic conditions "Could have more frequent/distractor bleeps for prioritisation" – Included three more scenarios for on-call simulation Conclusions: The success of the teaching programme was evident through positive feedback and good student attendance. By playing to the strength of foundation trainees as recent graduates, the programme complemented content-based teaching from more senior colleagues with sessions targeting practical F1 skills and exam specific needs of students. Early piloting also meant ability to constantly adapt the programme to enhance its benefit to the students.